2010
DOI: 10.1016/j.psyneuen.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Higher overcommitment to work is associated with higher plasma cortisol but not ACTH responses in the combined dexamethasone/CRH test in apparently healthy men and women

Abstract: Higher overcommitment to work is associated with higher plasma cortisol but not ACTH responses in the combined dexamethasone/CRH test in apparently healthy men and women Wirtz, P H; Siegrist, J; Schuhmacher, A; Hoefels, S; Maier, W; Zobel, A W Wirtz, P H; Siegrist, J; Schuhmacher, A; Hoefels, S; Maier, W; Zobel, A W (2009). Higher overcommitment to work is associated with higher plasma cortisol but not ACTH responses in the combined dexamethasone/CRH test in apparently healthy men and women. Psychoneuroendocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
11
0
2
Order By: Relevance
“…The glucocorticoids released from the adrenal cortex are required to resist the stressor but are also responsible for the pathological changes that are characteristic of the almost-exhaustion phase [ 44 ]. Consistent with this hypothesis, other studies have found similar increases in cortisol in subjects with an overcommitment to work [ 32 , 45 ] and a lack of control at work [ 46 ]. Physiologically rather than psychologically adverse conditions, such as asthma [ 47 ], rheumatoid arthritis [ 48 ] and atopic dermatitis [ 49 ], also lead to variations in the concentration of cortisol at rest; however, all of the subjects in this study were healthy thus this increased in cortisol levels is due to the psychological chronic stress.…”
Section: Discussionsupporting
confidence: 69%
“…The glucocorticoids released from the adrenal cortex are required to resist the stressor but are also responsible for the pathological changes that are characteristic of the almost-exhaustion phase [ 44 ]. Consistent with this hypothesis, other studies have found similar increases in cortisol in subjects with an overcommitment to work [ 32 , 45 ] and a lack of control at work [ 46 ]. Physiologically rather than psychologically adverse conditions, such as asthma [ 47 ], rheumatoid arthritis [ 48 ] and atopic dermatitis [ 49 ], also lead to variations in the concentration of cortisol at rest; however, all of the subjects in this study were healthy thus this increased in cortisol levels is due to the psychological chronic stress.…”
Section: Discussionsupporting
confidence: 69%
“…These associations are likely to differ in a sample including individuals who did not find employment again so quickly. Over-commitment, a measure of excessive striving, showed the strongest association with CMD in the current study and is associated with alterations in the hypothalamic-pituitary-adrenal axis system (Wirtz et al 2010) and stress responses in the sympathetic nervous system (Wirtz et al 2008). Over-commitment may capture elements of over-investment at work or work–life imbalance.…”
Section: Discussionmentioning
confidence: 55%
“…The association of cortisol excretion with work stress is debated in current research as chronic stress may attenuate as well as enhance hormonal responsiveness 37 38. Therefore, depending on the duration of exposure, increases or decreases in cortisol may have occurred in our sample, thus precluding a systematic pattern of response.…”
Section: Discussionmentioning
confidence: 94%